Electroencephalographic (EEG) coherence between visual and motor areas of the left and the right brain hemisphere while performing visuomotor task with the right and the left hand - Brežan, Simon (Zdravniški vestnik, 2007)
Unilateral limb movements are based on the activation of contralateral primarymotor cortex and the bilateral activation of premotor cortices. Performance of a visuomotor task requires a visuomotor integration between motor and visual cortical areas. The functional integration ( binding ) of different brain areas, is probably mediated by the synchronous neuronal oscillatory activity, which can be determined by electroencephalographic (EEG)coherence analysis. We introduced a new method of coherence analysis and compared coherence and power spectra in the left and right hemisphere for the nglat vs. left hand visuomotor task, hypothesizing that the increase in coherence and decrease in power spectra while performing the task would be greater in the contralateral hemisphere. We analyzed 6 healthy subjects and recorded their electroencephalogram during visuomotor task with the right or the left hand. For data analysis, a special Matlab computer programme was designed. The results were statistically analysed by a two-way analysis of variance, one-way analysis of variance and post-hoc t-tests with Bonferroni correction. We demonstrated a significant increase in coherence (p < 0.05) forthe visuomotor task compared to control tasks in alpha (8-23 Hz) in beta T (13-20 Hz) frequency bands between visual and motor electrodes. There were no significant differences in coherence nor power spectra depending on the hand used. The changes of coherence and power spectra between both hemispheres weresymmetrical. In previous studies, a specific increase of coherence and decrease of power spectra for the visuomotor task was found, but we found no conclusive asymmetries when performing the task with right vs. left hand. Thiscould be explained in a way that increases in coherence and decreases of power spectra reflect symmetrical activation and cooperation between more complex visual and motor brain areas.
Keywords: Electroencephalography; Elektroencefalografija; Motor Cortex; Motor Neurons; Motorična skorja; Motorični nevroni; možganska skorja; nevrofiziologija; vid; Vid, zaznava; Vidna skorja; Visual Cortex; Visual Perception